Urban growth and development in Asia - Chapman, Graham P (Ashgate, 1999)
"Proceedings from the 5th Asian Urbanisation Conference, held at the School of Oriental and African Studies in London in August 1997"; Includes bibliographical references; v. 1. Making the cities -- v. 2. Living in the cities